2021
DOI: 10.1007/s10853-021-06571-0
|View full text |Cite
|
Sign up to set email alerts
|

An organic hydrogel with high-strength, high-water retention properties for pressure sore protection

Abstract: The excellent mechanical properties and high-water retention of hydrogels will expand the application in the field of biomedical materials. In this work, we prepared hydrogel based on methacryloyl gelatin (GelMA), sulfobetaine and quaternized chitosan (QCS) by ''one-pot'' method. GelMA acts as cross-linking agent to cross-link the PSBMA network. QCS chains are interspersed in the PSBMA network. The hydrogel obtained after the polymerization initiated by ultraviolet light is further immersed in glycerin for sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Finally, the consecutively-printed IHPS can also work under a wide temperature range (−20 °C–90 °C). Typically under the conditions of −20 °C, the HS and LS hydrogels exhibited exceptional anti-freezing properties due to the presence of lithium chloride 32 , 33 and/or glycerol 34 , whereas the CS and AS hydrogels experienced partial freezing with weakly bound water and unfrozen water inside the hydrogel matrix (Supplementary Fig. 17 ) 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the consecutively-printed IHPS can also work under a wide temperature range (−20 °C–90 °C). Typically under the conditions of −20 °C, the HS and LS hydrogels exhibited exceptional anti-freezing properties due to the presence of lithium chloride 32 , 33 and/or glycerol 34 , whereas the CS and AS hydrogels experienced partial freezing with weakly bound water and unfrozen water inside the hydrogel matrix (Supplementary Fig. 17 ) 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan and cationic guar gum Oxidation, freeze-drying, carbonized Thermal/pH-responsive [39] Methacryloyl gelatin (GelMA) UV polymerization Mechanical strength, antibacterial, antifreezing [40] Polyvinyl alcohol (PVA) Solution casting…”
Section: Organic Hydrogelsmentioning
confidence: 99%
“…One is adding organic solvents directly to hydrogel prepolymer solutions, 37 and the other is replacing solvents of the hydrogel by soaking in organic solvents. 38 Hu et al reported a novel antifreezing conductive hydrogel by the one-pot method with glycerol. The antifreezing ability of the hydrogel increased with addition of 50%−70% glycerol.…”
Section: Introductionmentioning
confidence: 99%
“…There are generally two ways to incorporate organic solvents into hydrogels. One is adding organic solvents directly to hydrogel prepolymer solutions, and the other is replacing solvents of the hydrogel by soaking in organic solvents . Hu et al reported a novel antifreezing conductive hydrogel by the one-pot method with glycerol.…”
Section: Introductionmentioning
confidence: 99%